2017
DOI: 10.1111/anu.12650
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary geniposidic acid on growth performance, flesh quality and collagen gene expression of grass carp, Ctenopharyngodon idella

Abstract: This study was conducted to investigate the effects of dietary geniposidic acid (GA) on growth performance, flesh quality and collagen gene expression of grass carp (Ctenopharyngodon idella). The fish with an initial body weight of 47.1 ± 0.8 g were fed one of the seven diets, including control diet, Eucommia ulmoides (EU)-supplemented diet (20 g/kg) and GA-supplemented diets (200, 400, 600, 800 and 1,000 mg/kg GA) for 75 days. The growth performance and muscle proximate composition showed no difference among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…The previous studies indicated that CGA promoted the proliferation of fibroblasts in rats (Zhang, Li, Yun, You, & Luo, ), and GP stimulated the proliferation of ligament cells (Chen et al, ). In the present study, dietary CGA, GP and GAP supplementation increased muscle fibre density and reduced muscle fibre diameter of grass carp, and the similar results also have been reported by Sun et al (). Disappointedly, the three active compounds mixture showed a lower performance than the individuals.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The previous studies indicated that CGA promoted the proliferation of fibroblasts in rats (Zhang, Li, Yun, You, & Luo, ), and GP stimulated the proliferation of ligament cells (Chen et al, ). In the present study, dietary CGA, GP and GAP supplementation increased muscle fibre density and reduced muscle fibre diameter of grass carp, and the similar results also have been reported by Sun et al (). Disappointedly, the three active compounds mixture showed a lower performance than the individuals.…”
Section: Discussionsupporting
confidence: 92%
“…The variations in the results may due to the fish size, and smaller fish may be more sensitive to dietary CGA than bigger one. The dietary GP and GA showed no growth improvement effect on animals when compared with the CGA supplementation and control groups in the present study, which indicates that GP and GA are not the growth‐promoting active compounds in EU, similar findings to our previous studies (Sun et al, ). Furthermore, the mixture of GA:CGA:GP did not show a positive effect on growth improvement when compared to the individual addition.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Grass carp is an important freshwater fish cultured in Asia, especially in China. To improve the flesh quality of cultured grass carp, different nutritional strategies have been carried out in recent years, such as EU (Leng et al, ) and its active components chlorogenic acid (N. S. Li et al, ; Sun et al, ), geniposide (Sun et al, ), and geniposide acid (Sun, Xu, Li, Pan, & Leng, ). As the main active component in EU, quercetin may play a role in the growth‐promoting and flesh quality‐improving effects of EU.…”
Section: Introductionmentioning
confidence: 99%